Hospital educational education: the challenges and action to provide patients through pedagogical practice (Research, Society and Development, 2021)
The importance of hospital pedagogy in the care of hospitalized children and adolescents, who must have the right and access to teaching and learning in a playful way so that they do not miss the school year. The work of the pedagogue in this environment must be linked to pedagogical practices, as it is a process that tends to need attention and reflection so that education is more flexible for the children and adolescents who are there. Considering the information, the objective of this study is to address the challenges of the pedagogue in the hospital environment and to understand the processes of hospital pedagogy in the context of children/patients and the role of pedagogues. This document was built through searches carried out on research platforms such as Google Scholar, college repositories, among other websites. In general, it was possible to see that the work carried out by the hospital pedagogue is of paramount importance, because through this work hospitalized children and adolescents received in a correct and playful way the teaching-learning processes where they presented, through this work, a certain degree of development cognitive, having continued their studies within the hospital with enthusiasm and good self-esteem.